Dayah Education Model as the Basis for Character and Spirituality Development - Usman Usman; Bachtiar Akob; Asnawi Asnawi; Zulkifli Zulkifli; Aulia Rahman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This article discusses the role of the Dayah education model in Aceh in developing students' religious and social character, and its relevance as an educational institution grounded in Islamic values amid modernization. This study uses a qualitative-descriptive case study approach to explore in depth the role of Dayah education in character formation. Data was obtained from primary sources (in-depth interviews with teungku, students, and Dayah managers) and secondary sources (curriculum documents, diaries, and kitab kuning). Data collection techniques include participatory observation of learning activities, semi-structured interviews, and documentation studies. The data were analyzed thematically through coding, pattern identification, and interpretation to uncover the values of character education and Dayah adaptation strategies in the modern era. Triangulation of sources and methods is carried out to ensure the validity of the data. The study's findings show that the Dayah functions not only as a center for religious learning but also as a fortress in maintaining the Islamic identity and local culture of the Acehnese people. This research contributes to the literature on character-based Islamic education. It shows that Dayah has the potential to address the challenges of globalization by integrating modern practical skills. Dayah can serve as a relevant and sustainable model of education that maintains tradition while meeting the needs of the times.